The Voice-Rate Dialog System for Consumer Ratings - Zweig, Geoffrey; Nguyen, Patrick; Ju, Y. C.; Wang, Ye-Yi; Yu, Dong; Acero, Alex (INTERSPEECH, 2007)
Voice-Rate is an experimental dialog system that makes product and business ratings available to consumers via a toll-free phone number. By calling Voice-Rate, users can access the ratings of more than one million products, a quarter million local businesses (restaurants), and three thousand national businesses. This paper describes the Voice Rate system, and solutions to three key technical challenges: robust name-matching, efficient disambiguation, and review synthesis for telephone playback. Voice-Rate can be accessed by calling 1-877-456-DATA (toll-free) within the U.S.